2022
DOI: 10.1177/10760296221113346
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Indices and Outcome in Patients with Acute Venous Thromboembolism

Abstract: Background Cellular indices provide integrative information about systemic inflammation status which is readily available from routine laboratory parameters. This study aimed to evaluate the prognostic role of three cellular indices in patients with venous thromboembolism (VTE). Methods The RIETE registry database was used to determine the association between the baseline neutrophil-to-lymphocyte-ratio (NLR), platelet-to-lymphocyte-ratio (PLR) and systemic-immune-inflammation-index (SII) for 90-day adverse out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Siddiqui et al found that of 4487 patients, 152 (3.4%) suffered major bleeding and 484 (11%) died, indicating there may be an increased risk of major bleeding or death with higher baseline NLR values among patients with VTE. 41 In addition, a large population-based cohort showed similar associations between mortality and VTE. 42 Higher NLRs and PLRs have also been shown to be associated with poorer short-term and long-term prognosis, increased mortality, and longer hospitalization in patients with PE.…”
Section: Discussionmentioning
confidence: 89%
“…Siddiqui et al found that of 4487 patients, 152 (3.4%) suffered major bleeding and 484 (11%) died, indicating there may be an increased risk of major bleeding or death with higher baseline NLR values among patients with VTE. 41 In addition, a large population-based cohort showed similar associations between mortality and VTE. 42 Higher NLRs and PLRs have also been shown to be associated with poorer short-term and long-term prognosis, increased mortality, and longer hospitalization in patients with PE.…”
Section: Discussionmentioning
confidence: 89%
“…Duplicates amongst those were removed leaving 1568 results. One thousand five hundred forty of those were excluded due to non-relevance and 28 studies were selected for full-text analysis and 15 9,[13][14][15][16][20][21][22][23][24][25][26][27][28][29] were included.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11][12] Similarly, numerous studies have examined the relationship between NLR and PLR and the outcomes of PE. [13][14][15][16] While some studies 15,16 indicate that these indices are predictive of mortality, few suggest otherwise. 13,14 Given the variable results, there is a need for a comprehensive systematic review.…”
Section: Introductionmentioning
confidence: 99%
“… 29 Siddiqui et al found VTE patients with higher baseline NLR values were at an increased risk of major bleeding or death. 30 In addition to predicting mortality, Jia et al found NLR was predictive of right ventricular dysfunction. 31 A previous meta-analysis including 1424 patients from 6 retrospective studies found high NLR has a sensitivity of 77% and a specificity of 74% in predicting short-term mortality.…”
Section: Discussionmentioning
confidence: 99%